Evolutionarily distinct amphibians are disproportionately lost from human‐modified ecosystems. (21st August 2018) - Greenberg, D. A.; Palen, W. J.; Chan, K. C.; Jetz, W.; Mooers, A. Ø.
Abstract: Humans continue to alter terrestrial ecosystems, but our understanding of how biodiversity responds is still limited. Anthropogenic habitat conversion has been associated with the loss of evolutionarily distinct bird species at local scales, but whether this evolutionary pattern holds across other clades is unknown. We collate a global dataset on amphibian assemblages in intact forests and nearby human‐modified sites to assess whether evolutionary history influences susceptibility to land conversion. We found that evolutionarily distinct amphibian species are disproportionately lost when forested habitats are converted to alternative land‐uses. We tested the hypothesis that grassland‐associated amphibian lineages have both higher diversification and are pre‐adapted to human landscapes, but found only weak evidence supporting this. The loss of evolutionarily distinct amphibians with land conversion suggests that preserving remnant forests will be vital if we aim to preserve the amphibian tree of life in the face of mounting anthropogenic pressures.